Modular platforms for the assembly of self-adjuvanting lipopeptide-based vaccines for use in an out-bred population. Issue 3 (16th January 2020) - Zeng, Weiguang; Horrocks, Kylie J.; Tan, Amabel C.L.; Wong, Chinn Yi; Chua, Brendon Y.; Jackson, David C.
Highlights: Two novel modular approaches for assembly of lipopeptide-based vaccines developed. These vaccines are self-adjuvanting and work in four different strains of mice. Different chemical linkages and configurations of vaccine constructs investigated. Stable bond between Pam2Cys and B cell epitope critical for antibody induction. Abstract: To facilitate the preparation of synthetic epitope-based self-adjuvanting vaccines capable of eliciting antibody responses in an out-bred population, we have developed two modular approaches. In the first, the Toll-like receptor 2 agonist Pam2 Cys and the target antibody epitope are assembled as a module which is then coupled to a carrier protein as a source of antigens to stimulate T cell help. A vaccine candidate made in this way was shown to induce a specific immune response in four different strains of mice without the need for extraneous adjuvant. In the second approach, three vaccine components in the form of a target antibody epitope, a T helper cell epitope and Pam2 Cys, were prepared separately each carrying different chemical functional groups. By using pH-mediated chemo-selective ligations, the vaccine was assembled in a one-pot procedure. Using this approach, a number of vaccine constructs including a lipopeptide-protein conjugate were made and also shown to elicit immune responses in different strains of mice. These two modular approaches thus constitute a powerful platform for the assembly of self-adjuvanting lipopeptide-based vaccines that can potentially be used to induce robust antibody responses in an outbred population. Finally, our study of the impact of chemical linkages on immunogenicity of a lipopeptide vaccine shows that a stable covalent bond between Pam2Cys and a B cell epitope, rather than between Pam2Cys and T helper cell epitope is critical for the induction of antibody responses and biological efficacy, indicating that Pam2Cys functions not only as an adjuvant but also participates in processing and presentation of the immunogen.